1997
DOI: 10.1200/jco.1997.15.4.1302
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy with hematopoietic rescue in patients with stage III to IV ovarian cancer: long-term results.

Abstract: HDC followed by autologous stem-cell support is a well-tolerated therapeutic approach for patients with poor-prognosis ovarian carcinoma. In this report, the 59.9% survival of 53 patients at 5 years must be compared to the 20% to 30% 5-year survival observed after conventional therapy. These results should be confirmed by an ongoing prospective randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
3
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 15 publications
7
59
3
2
Order By: Relevance
“…According to our experience in autologous transplantation, the prognosis of the patient was poor and intensive chemotherapy followed by autologous peripheral blood stem cell transplantation was unlikely to be able to cure the disease. 5 Because of the good performance status of the patient, a bone marrow allograft was proposed with an HLA-identical, sex mismatched adult sibling.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our experience in autologous transplantation, the prognosis of the patient was poor and intensive chemotherapy followed by autologous peripheral blood stem cell transplantation was unlikely to be able to cure the disease. 5 Because of the good performance status of the patient, a bone marrow allograft was proposed with an HLA-identical, sex mismatched adult sibling.…”
Section: Case Reportmentioning
confidence: 99%
“…According to our experience in autologous transplantation, the prognosis of the patient was poor and intensive chemotherapy followed by autologous peripheral blood stem cell transplantation was unlikely to be able to cure the disease. 5 Because of the good performance status of the patient, a bone marrow allograft was proposed with an HLA-identical, sex mismatched adult sibling.Before the allograft procedure the patient presented with abdominal tumor nodules, a progression of pulmonary metastatic lesions and the elevation of CA125 (169 U). The conditioning regimen consisted of myleran 4 mg/kg daily for 4 consecutive days and cyclophophamide 50 mg/kg daily for 4 consecutive days.…”
mentioning
confidence: 99%
“…Highdose chemotherapy improved PFS but had failed to improve OS. [3][4][5] New drugs such as topotecan lead to a biological response but induced severe hematologic toxicities. 17 Since Child et al had demonstrated in kidney cancer a GvT effect, the first potential evidence of allogeneic antitumoral response in solid tumors, 18 allo HCT was the next logical step.…”
Section: Discussionmentioning
confidence: 99%
“…Among these patients, 1 was in CR at the time of allo HCT, while 7 were in PR, 11 in SD and 13 had PD. The median number of prior chemotherapy lines was 3 [range [2][3][4][5][6][7]. Seventeen donors were female (53%) with a median age of 46 years (range 27-65; Table 1).…”
Section: Patients' and Donors' Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation